2020
DOI: 10.1200/jco.2020.38.15_suppl.6507
|View full text |Cite
|
Sign up to set email alerts
|

TPExtreme randomized trial: Quality of Life (QoL) and survival according to second-line treatments in patients with recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC).

Abstract: 6507 Background: TPExtreme trial comparing EXTREME regimen to the taxane-based TPEx confirmed the encouraging survival results of the TPEx regimen, despite lack of significant overall survival (OS) increase, with a significantly lower toxicity than the EXTREME regimen. Herein, the QoL and exploratory analyses of survival according to 2nd line treatments focusing on immunotherapy (IO) are presented. Methods: Randomized (1:1), open-label trial. Main inclusion criteria were R/M HNSCC not suitable for loco-region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…In a phase 3 clinical trial of breast cancer, combination therapy of nab-paclitaxel and the anti PD-L1 inhibitor atezolizumab showed prolonged PFS over nab-paclitaxel alone in the PD-L1-positive subgroup ( 33 ). Besides, in the exploratory analysis of 2nd-line therapy after either TPExtreme regimen, which was combination therapy of docetaxel+CDDP+Cmab, or ETREME regimen in R/M HNSCC, patients treated with ICI showed longer OS compared with those with chemotherapy in both regimens; however, this trend was more potent in TPExtreme (interaction test p = 0.077) ( 34 ). This result also suggested that the use of taxane prior to ICI presumably augments the effect of subsequent ICI and supports our hypothesis that PTX may enhance the response to nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 3 clinical trial of breast cancer, combination therapy of nab-paclitaxel and the anti PD-L1 inhibitor atezolizumab showed prolonged PFS over nab-paclitaxel alone in the PD-L1-positive subgroup ( 33 ). Besides, in the exploratory analysis of 2nd-line therapy after either TPExtreme regimen, which was combination therapy of docetaxel+CDDP+Cmab, or ETREME regimen in R/M HNSCC, patients treated with ICI showed longer OS compared with those with chemotherapy in both regimens; however, this trend was more potent in TPExtreme (interaction test p = 0.077) ( 34 ). This result also suggested that the use of taxane prior to ICI presumably augments the effect of subsequent ICI and supports our hypothesis that PTX may enhance the response to nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other strategies are worth discussing. In the TPExtreme study, a first line chemotherapy with a taxane (TPEx) followed by second line with immunotherapy yields a 21.9 month median survival [37]. In the end, in order to determine which would be the best strategy, a randomized trial should be conducted comparing TPEx followed by immunotherapy vs. pembrolizumab + chemotherapy in first line.…”
Section: Keynote-048 Study Conclusionmentioning
confidence: 99%
“…TPEx regimen was associated with 30% grade 4 adverse events, which was signi cantly lower than the 43% incidence reported with the EXTREME schema. Furthermore, an exploratory analysis of this trial showed a better quality of life in patients who received TPEx, mainly in global health status, physical functioning, role functioning, and scores of appetite20 .Remarkably, real-world data in this setting is scarce. Before the GORTEC trial, Guigay and collaborators presented the results of 30 patients treated with TPEx at Gustave Roussy Institute between 2011 and 201321 .…”
mentioning
confidence: 89%